If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22x + -32 = 13x + 4 Reorder the terms: -32 + 22x = 13x + 4 Reorder the terms: -32 + 22x = 4 + 13x Solving -32 + 22x = 4 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. -32 + 22x + -13x = 4 + 13x + -13x Combine like terms: 22x + -13x = 9x -32 + 9x = 4 + 13x + -13x Combine like terms: 13x + -13x = 0 -32 + 9x = 4 + 0 -32 + 9x = 4 Add '32' to each side of the equation. -32 + 32 + 9x = 4 + 32 Combine like terms: -32 + 32 = 0 0 + 9x = 4 + 32 9x = 4 + 32 Combine like terms: 4 + 32 = 36 9x = 36 Divide each side by '9'. x = 4 Simplifying x = 4
| 7x+6=17-4x | | 0.3x+0.5x+x=2x+0.15 | | 2x+10x+72=180 | | 225-x/2=y | | 17×8/3 | | (3x-4y)-120=300 | | 2(-4+x)+y=5 | | x+2(3x-4)+5x=16 | | 7c-4=14 | | -4x+2y+4=0 | | 3x/2x-4 | | 2x+6=60-9x | | v=9*9*12.5/3 | | 15w+30=2 | | 3x^3+4x+16=0 | | a/2a | | 6-8=38 | | -8t+-32=-32 | | 9x+7=15+7x | | x+6=x*x+120 | | 2-8.9y+54tg= | | 2f-14=-12 | | 10s-50=-77 | | 6x+3=-9+3x | | -c+4=-1 | | 8x+6=20+6x | | y=15x-8 | | _(*+3)=7 | | 18s+42=78 | | 14l+7=105 | | (7x+1)+(4x-2)=120 | | (7x+1)+(4x-2)=10 |